The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1980-220x-reeusp-2022-0394pt
|View full text |Cite
|
Sign up to set email alerts
|

Espiritualidade, religiosidade e suas representações para pessoas que vivem com HIV: o cotidiano e suas vivências

Abstract: RESUMO Objetivo: Descrever o processo de viver com HIV/Aids no cotidiano de pessoas vivendo com HIV em sua interface com as representações sociais da espiritualidade e da religiosidade. Método: Pesquisa qualitativa, apoiada pela teoria das representações sociais. Realizou-se entrevista semiestruturada com 32 pessoas em tratamento para HIV num ambulatório especializado em HIV/Aids. Análise realizada com suporte do software IRAMUTEQ. Resultados: Os participantes foram em sua maioria homens, com idade superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…From the presented data, the hypothesis arises that it is the same representation, which would be equivalent to saying that, for the participants, religiosity and spirituality are learned as the same phenomenon or that, at least in large part of its symbolic and representational construction, there is an important overlapping of elements and meanings. This result, in a way, is not surprising, given the fact that other studies have been found in the literature that worked with spirituality and religiosity as objects and/or representational phenomena, which also concluded that they constituted the same representation 2 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…From the presented data, the hypothesis arises that it is the same representation, which would be equivalent to saying that, for the participants, religiosity and spirituality are learned as the same phenomenon or that, at least in large part of its symbolic and representational construction, there is an important overlapping of elements and meanings. This result, in a way, is not surprising, given the fact that other studies have been found in the literature that worked with spirituality and religiosity as objects and/or representational phenomena, which also concluded that they constituted the same representation 2 .…”
Section: Discussionsupporting
confidence: 65%
“…The object of study of this article refers to the representations of spirituality and religiosity for women who belong to Afro-diasporic religions, specifically those who are faithful to Umbanda and Candomblé. Its importance is due to the theoretical hypothesis that, despite being distinct concepts and phenomena that can happen in different ways, and even separately in specific contexts, they introduce themselves as the same representation for the studied Brazilian social groups 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings presented, it is possible to identify the central nucleus and describe the structure of the CHA's thinking about DVAW. Thus, as an analysis criterion for defining an element as central, a minimum of three methods were established indicating centrality of the element 21 .…”
Section: Resultsmentioning
confidence: 99%
“…It is noticed that the disrespect for the CHAs can be understood as an attitude or behavior of the aggressor in relation to the woman, being the trigger of the domestic violence episodes. The central nucleus elements generate a global meaning of the representation, have strong historical and ideological roots and are consensual in the group 21 .…”
Section: Discussionmentioning
confidence: 99%